Get the X's on the same side of the equation by subtracting 3x from both sides, then get the constants on the same side by subtracting 5 from each side. You'll simplify it to 6x-3x=17-5, resulting in 3x=12 or x=4...

Posted on Nov 14, 2014

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

Let's take 2x^2 - 10x +12 and divide it by x-2.

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

Oct 03, 2014 | Office Equipment & Supplies

x=-2

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

Feb 08, 2014 | Office Equipment & Supplies

-60-45x-8x=26-6x+54

-60-53x=80-6x

-53x+6x=140

-47x=140

x=-140/47

-60-53x=80-6x

-53x+6x=140

-47x=140

x=-140/47

May 19, 2012 | SoftMath Algebrator - Algebra Homework...

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

Dear Anne I am old school but I think it works lide this..

6x+21+4x=-9

so add 9 to both sides

6x+30+4x=0

so 6x+4x+30=0

so 10x+30=0

so x= -3

I hope this helps.

6x+21+4x=-9

so add 9 to both sides

6x+30+4x=0

so 6x+4x+30=0

so 10x+30=0

so x= -3

I hope this helps.

Oct 09, 2011 | Office Equipment & Supplies

For 3x(7x+6x)=0, x=0

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

Jun 22, 2011 | Acer Aspire One Netbook

you have to make sure you are using the correct format for your drive i.e (+/-)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 8X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM, 4X BD-ROM, 4X BD-R, 2X BD-RE, 4X BD-ROM DL (double-layer), 4X BD-R DL (double-layer), 2X BD-RE DL (double-layer)
- Write: 24X CD-R, 16X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-RW, 6X DVD+RW, 5X DVD-RAM, 4X DVD+R DL (double-layer), 4X DVD-R DL (double-layer)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 6X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM
- Write: 24X CD-R, 24X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 6X DVD-RW, 8X DVD+RW, 5X DVD-RAM

Apr 09, 2011 | Acer Computers & Internet

The first step here is to draw a rough sketch of the two curves, and find the two points they meet. If you set x^3-6x^2+8x = x^3-4x, then you can rearrange this into the quadratic equation 6x^2-12x = 0. Solving this tells you x=0 or 2 : these are the two x values where the curves meet, and they give the bounds on your integral.

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

May 27, 2010 | Computers & Internet

6x+5(x+9y)+7y

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

Nov 21, 2009 | Video Game Consoles & Games

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

Aug 17, 2017 | The Computers & Internet

43 people viewed this question

Usually answered in minutes!

×